Hybrid Positron Emission Tomography/Magnetic Resonance Imaging: Challenges, Methods, and State of the Art of Hardware Component Attenuation Correction. Issue 10 (October 2016) - Paulus, Daniel H.; Quick, Harald H.
Abstract : Abstract: Attenuation correction (AC) is an essential step in the positron emission tomography (PET) data reconstruction process to provide accurate and quantitative PET images. The introduction of PET/magnetic resonance (MR) hybrid systems has raised new challenges but also possibilities regarding PET AC. While in PET/computed tomography (CT) imaging, CT images can be converted to attenuation maps, MR images in PET/MR do not provide a direct relation to attenuation. For the AC of patient tissues, new methods have been suggested, for example, based on image segmentation, atlas registration, or ultrashort echo time MR sequences. Another challenge in PET/MR hybrid imaging is AC of hardware components that are placed in the PET/MR field of view, such as the patient table or various radiofrequency (RF) coils covering the body of the patient for MR signal detection. Hardware components can be categorized into 4 different groups: (1) patient table, (2) RF receiver coils, (3) radiation therapy equipment, and (4) PET and MR imaging phantoms. For rigid and stationary objects, such as the patient table and some RF coils like the head/neck coil, predefined CT-based attenuation maps stored on the system can be used for automatic AC. Flexible RF coils are not included into the AC process till now because they can vary in position as well as in shape and are not accurately detectable with the PET/MR system. This work summarizes challenges, established methods, new concepts, and the state of art in hardware component AC in the context of PET/MR hybrid imaging. The work also gives an overview of PET/MR hardware devices, their attenuation properties, and their effect on PET quantification.